A criança com transtorno do espectro autista (TEA) e o professor: uma proposta de intervenção baseada na experiência de aprendizagem mediada (EAM) - Macêdo, Cláudia Roberto Soares de (2015)
The presence of students with Autism Spectrum Disorder (ASD) in regular schools has increased and with it, the need to develop interventional strategies that enhance their learning. One of the tools that can facilitate this process is Mediated Learning, defined as an interaction style where the teacher selects, modifies, enhances, and interprets environmental stimuli in order to promote student learning. In recent years several studies have used the Mediated Learning Experience Scale (MLE; Lidz, 1991) as a tool to assess the mediator behavior. These studies have suggested that the EAM Scale can provide important guidelines for planning educational interventions, particularly those involving students with special needs. In order to extend these findings, this study aimed to evaluate the effects of an intervention based on the Mediated Learning Experience on social / academic skills of a child with ASD, enrolled in the 4th grade of a regular elementary school. This collaborative study was held in the city of Parnamirim, state of Rio Grande do Norte, in 2014. A 9-year old boy with ASD and his teacher participated in the study. The research used a quasi-experimental A-B design (baseline and treatment) to evaluate the teacher's behavior. Qualitative procedures were also used to analyze the dyad´s responses. Teacher and student behaviors were observed in three school routines during baseline. Based on the results of this phase, a training program was designed for the teacher. Dyad behavior was analyzed again after training in the same routines. The results of this phase showed qualitative and quantitative changes in levels of teacher mediation. Additionally, data indicated that the child enhanced his social and academic skills during the intervention.